Neonate Presenting with Covid Infection, Cytokine Storm and Sepsis: A Case Report - Mallesh Kariyappa; Aparna Dutt; Sahana Devadas (Research Highlights in Disease and Health Research Vol. 8, 2023)
Background: COVID-19, a clinical syndrome caused by the coronavirus (SARS-CoV-2) became a pandemic following an outbreak of viral pneumonitis, first identified in Wuhan, China. The disease manifestations vary ranging from mild upper respiratory tract infection to severe pneumonitis, acute respiratory distress syndrome (ARDS) and even death. Although most of the neonatal cases are asymptomatic rarely they can present with cytokine storm mimicking with similar features of sepsis. Cytokine storm can occur following the infection leading to tissue damage, multiorgan involvement and even death. Case Report: This is a case report of SARS-CoV19 positive neonate presenting with sepsis and cytokine storm. 5 day old baby born to SARS –COVID 19 positive mother presented with fever and investigations showed elevated total counts with neutrophilic predominance, thrombocytopenia suggestive of sepsis and increased inflammatory markers suggestive of cytokine storm. Blood culture was sent and baby was started on intravenous antibiotics .In view of cytokine storm intravenous dexamethasone 0.5 mg/kg/day was given intravenously for 5 days. Neonate recovered from illness after 1 week as evidenced clinically and by inflammatory markers before discharge. This case report shows the possibility of having both sepsis and cytokine storm in a SARS-CoV19 positive neonate.